Laporan Kasus: Terapi Covid-19 pada Pasien dengan Komorbid Hipertensi: Case Report: Covid-19 Therapy in Patients with Comorbid Hypertension - Putri Dina Mahera Laily (Jurnal Sains dan Kesehatan, 2022)
Corona Virus Desease 2019 (COVID-19), is a disease caused by corona virus. According to the World Health Organization (WHO), COVID-19 is a tragedy in the world of global health. The main clinical manifestations are cough, fever, shortness of breath and in some cases can cause multiple organ failure, septic shock and metabolic acidosis which is difficult to correct. Where people who are elderly and have chronic disease generally have a poor prognosis. Prompt and appropriate therapy is expected to save patients. Until now, scientific evidence regarding the effectiveness and safety of these therapies is still very little. This study aims to evaluate the effectiveness and safety of COVID-19 therapy in COVID-19 patients with comorbid hypertension. The therapy used in this patient was azithromicin, ceftriaxone, levofloxacin and meropenem; Antiviral therapy was given hydroxychloroquine; symptomatic therapy for fever was given paracetamol; hypertension therapy was given amlodipine; Support therapy was given salbutamol and dexamethasone; Additional therapy was given vitamin C 1000 mg / 24 hours, and zinc. There was no worsening effect on the patient after receiving this therapy. Patients get treatment at RSUP Dr. Sardjito then was discharged after treatment without any complaints and with PCR swabs were negative results. Keywords: Therapy, COVID-19, Comorbid, Hypertensi